2019
DOI: 10.1177/1534734619832738
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Low-Frequency, Noncontact Airborne Ultrasound Therapy (Glybetac) For Neuropathic Diabetic Foot Ulcers: A Randomized, Double-Blind, Sham-Control Study

Abstract: The diabetic foot ulcer (DFU) healing rates remain dismally low. Therefore, many adjunctive therapies have been evaluated including ultrasound therapy. The prior studies with noncontact, low-frequency ultrasound were retrospective, single arm, unblinded, or with historical controls. The aim of the present study was to compare the efficacy of noncontact, low-frequency airborne ultrasound (Glybetac) therapy with sham therapy added to standard treatment in patients with neuropathic, clinically infected, or noninf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 35 publications
(66 reference statements)
0
37
0
2
Order By: Relevance
“…In particular, Rastogi et al 140 observed in a 4-week follow-up period a reduction of the wound area in 97.1% and a percentage of wound healing of 23.5% in the US group compared with the 73.1% (P = .042) and the 11.5% (P = .033) observed in control group, respectively. The results of Ennis et al 144 study also showed a double percentage of wound healing within 90 days and a shorter mean time to healing in group using US therapy compared with the control group.…”
Section: Ultrasound In the Management Of Diabetic Foot Ulcersmentioning
confidence: 94%
See 3 more Smart Citations
“…In particular, Rastogi et al 140 observed in a 4-week follow-up period a reduction of the wound area in 97.1% and a percentage of wound healing of 23.5% in the US group compared with the 73.1% (P = .042) and the 11.5% (P = .033) observed in control group, respectively. The results of Ennis et al 144 study also showed a double percentage of wound healing within 90 days and a shorter mean time to healing in group using US therapy compared with the control group.…”
Section: Ultrasound In the Management Of Diabetic Foot Ulcersmentioning
confidence: 94%
“…The therapeutic use of US has been evaluated in many studies conducted in wounds of different origin, including DFUs. [137][138][139][140][141][142][143][144][145][146][147] The therapeutic-frequency spectrum ranges from 20 to 120 kHz and is applied to wounds directly 148 or to periwound sites or by subaqueous immersion. 149 The rationale of therapeutic US application is based on 2 main mechanisms of action that are involved in the wound healing process [149][150][151][152] : cavitation and microstreaming.…”
Section: Ultrasound In the Management Of Diabetic Foot Ulcersmentioning
confidence: 99%
See 2 more Smart Citations
“…At least 25% of diabetic patients are likely to develop diabetic foot, and 85% of diabetic foot ulcers can eventually lead to amputation [7,8]. Epidemiological studies have reported that due to ischemia caused by diabetic nephropathy or peripheral vascular disease, diabetic distal limb neuropathy might occur, and then develops into diabetic foot [9].…”
Section: Introductionmentioning
confidence: 99%